Development of Ginger Honey Candy Supplements with Propolis - Duong, Ngan Phuong Vo; Nguyen, Anh Lan; Pham, Truong Nhat; Nguyen, Trong Quoc; Cao, Loan Thi Thanh (Journal of Technical Education Science, 2025)
The study aimed to develop a hard candy utilizing Vietnam’s abundant honey supply, combined with ginger essential oil and propolis, to create a candy that enhances resistance. The candy formulation included sucrose, water, citric acid, glucose syrup, and honey, ginger essential oil and propolis, with honey concentrations tested at 10%, 15%, 20% and 30%. Sensory evaluation, conducted according to TCVN 3215–79 standard with 30 panelists, indicated the 10% honey formulation as the most preferred. Among propolis concentrations (0.5 – 2%), the candy containing 0.5% propolis was favored and used in subsequent formulations to determine the ginger essential oil level. Candies containing ginger essential oil (GEO) at 10, 20, 30, and 40 µL, showing that candies with GEO had significantly higher total polyphenol content than other commercial candies. The results showed that the combination of honey, propolis and ginger essential oil enhances the antioxidant capacity of the candy. Therefore, the honey ginger candy supplemented with propolis has a distinctive color and flavor while retaining the inherent antioxidant properties of natural ingredients like propolis and ginger.